Developing Supplementary Writing Material For University Students - Caltira Rosiana (Dharma Pendidikan, 2017)
The objective of this particular research and development is to produce the supplementary materials to encourage the students’ academic writing for University students in second semester. Based on the preliminary study conducted by the researcher, it was discovered that most of the learner lacked motivation to create a simple paragraph in writing skill because the instructional document problems. To achieve the aim of this study, R&D proposed by Borg and Gall (1983: 771-789) as follows the need assessment and reference, developing material, product validation, implementation of the product and final product. The product designed with Contextual Teaching Learning (CTL) method which has the challenging activities with relating, experiencing, applying, collaborating, and transferring. To collect the relevant information, the researcher used guided questionnaire for students, interviews for teachers, a checklist form and suggestions for expert validation. The results of the data analysis from expert validation indicated that there were some strong and weak points of the materials developed so that the weak ones needed to be revised. To know the applicability of material developed, it is needed to apply the product in the real field. The implication of this product was divided into three points namely, the students could achieve the writing skill around 87%, the students’ motivation also improve around 88% and around 88% of the student could give the feedback about writing problem. Finally, the researcher suggests the teachers and students to use this supplementary material in teaching writing activities for the second semester students of University to enhance students’ ability in writing.